Konsep Pendidikan Modern Mahmud Yunus dan Kontribusinya Bagi Lembaga Pendidikan Islam di Indonesia - Manti, Biltiser Bachtiar; Husaini, Adian; Mujahidin, Endin; Hafidhuddin, Didin (Ta’dibuna: Jurnal Pendidikan Islam, 2016)
This research is motivated by the attitude of Muslim ambiguity in facing modernity which its existence is necessity and can not be rejected in any way. The product of modernity has roiled throughout the joints and pulse of human life without any rebellion. Because he is present with a friendly and pragmatic smile, so able to lull and make forget the impacts. The author formulates this research on the concept of modern education Mahmud Yunus and its relevance to modern education now and how its contribution to modern educational institutions in Indonesia. This study aims to get a picture of modern educational thinking Mahmud Yunus and its relevance to the birth of modern educational institutions in Indonesia. This research is library research, where the data obtained through primary data sources and secondary data, either through the source books of Mahmud Yunus figures directly or from reading materials and internet searching and interviews that the author describes by arranging them according to the theme and issues, especially issues related to the modernization of Islamic education in Indonesia. The concept of modern education Mahmud Yunus is a radical renewal of the education system by taking into account the needs and demands of society, without destroying the existing order. So the offer of modernization of education Mahmud Yunus, in the application of its implementation does not get opposition from anyone, both internal and ekster-nal. While his contribution to the birth of modern educational institutions in Indonesia; In the first place, institutional modernization, Mahmud Yunus is among those who pioneered the need to change the teaching system from the individual ones as applied in the pesantren using the sorogan or weton method. Secondly, the modernization in curriculum where Mahmud Yunus was the first to pioneer the existence of an integrated curriculum, a curriculum combining religious knowledge and general science in Islamic educational institutions, especially in developing Arabic teaching. Third, modernization in the field of learning, Mahmud Yunus is recognized by educational experts as a way hacker for the birth of new methods of Islamic education in Indonesia and he made a new teaching method that he introduced with the name al-thariqah al-mubasyarah (direct methode) that teaches various components science of Arabic. From the thought of Mahmud Yunus is found a new concept, namely; "ICT-based Modern Madrasahs" from the elaboration of the modernization concept both from the institutional side, the curriculum, the method of learning and producing a reliable educator in the hope of becoming a new paradigm for the world of Islamic education in the world and Indonesia in particular. Keywords: modern education, islamic education institution, integrated curriculum